Compartmentalized Antimicrobial Defenses in Response to Flagellin. Issue 5 (May 2018) - Vijayan, Aneesh; Rumbo, Martin; Carnoy, Christophe; Sirard, Jean-Claude
Abstract : Motility is often a pathogenicity determinant of bacteria targeting mucosal tissues. Flagella constitute the machinery that propels bacteria into appropriate niches. Besides motility, the structural component, flagellin, which forms the flagella, targets Toll-like receptor 5 (TLR5) to activate innate immunity. The compartmentalization of flagellin-mediated immunity and the contribution of epithelial cells and dendritic cells in detecting flagellin within luminal and basal sides are highlighted here, respectively. While a direct stimulation of the epithelium mainly results in recruitment of immune cells and production of antimicrobial molecules, TLR5 engagement on parenchymal dendritic cells can contribute to the stimulation of innate lymphocytes such as type 3 innate lymphoid cells, as well as T helper cells. This review, therefore, illustrates how the innate and adaptive immunity to flagellin are differentially regulated by the epithelium and the dendritic cells in response to pathogens that either colonize or invade mucosa. Trends: The flagellum, mostly formed of flagellin, propels bacteria. The conserved sequences at the termini of flagellin are essential for motility, and also for immuno-sensing through Toll-like receptor 5 (TLR5). Motility allows pathogenic bacteria to colonize mucosal surfaces. The expression of flagellin is a danger signal which informs mucosa that there is a bacterial threat. TLR5-dependent detection of flagellin at the apical pole of epithelial cells drives recruitment of phagocytes in mucosa and the production of antimicrobial molecules. Epithelial cells also educate dendritic cells to elicit adaptive immunity. Epithelium breaching by motile pathogenic bacteria, and the sensing of flagellin by tissue-resident dendritic cells, stimulates IL-22 production by type 3 innate lymphoid cells and innate defenses. This signaling also promotes differentiation of lymphocytes and modulation of adaptive immunity.